Introduction to the concept of mental disorders diagnosis in DSM-5 - Czernikiewicz, Andrzej (Current Problems of Psychiatry, 2012)
So it will be! ... ... the next version of the diagnostic manual of the American Psychiatric Association, the DSM-5.